The Principle Of Justice Ratio Decidendi Of The Judge In Decision Number 813 K/PID2-23 - Missleini Missleini; Evi Retno Wulan (Fakultas Hukum Dehasen, 2024)
Decision Number 813 K/PID2-23 is of deep concern in the legal field, especially regarding the analysis of the ratio decidendi principle of justice applied by judges in determining decisions. In this context, it is important to understand the various aspects that are taken into consideration by judges in making fair and just decisions. In this discussion, we will explore several key aspects that need to be considered in analyzing the principle of justice in Decision Number 813 K/PID2-23. These aspects include the principles of proportionality in the application of law, equality before the law, legal certainty, and rehabilitation and resocialization. This research also refers to the relevance and implications of the decision for the development of law and justice in society. It is hoped that this discussion can provide deeper insight into how the principle of justice ratio decidendi of judges is applied in the context of complex criminal cases such as Decision Number 813 K/PID2-23.